Competences in the Field of Finance – Results of a Population Survey - Szobonya, Réka (Public Finance Quarterly, 2021)
During the global pandemic, the frequency of digital financial services has increased, one of the reasons for which may be the fear of infection, which is not necessarily based on prudent orientation. Nowadays, to navigate in the increasingly digital financial market, it is essential to have the right tools and competencies that help in the use of services. During the population survey conducted in the summer of 2019 – before the outbreak of the coronavirus epidemic –, I examined the level of digital competencies in managing finances and its correlations with the level of financial knowledge and the use of electronic financial services. I researched possible gender differences regarding digital competencies, and whether the use of digital tools is dependent of demographic characteristics. I found out that the competencies of women and men led to similar results. However, the development level of one’s place of residence is related to the frequency of use of electronic devices.